Characterization of VigiBase reports on tinnitus associated with bisoprolol—An exploratory and descriptive study. Issue 3 (6th May 2021) - Watson, Sarah; Taavola, Henric; Attalla, Marian; Kaminsky, Elenor; Yue, Quin‐Ying
Abstract: The aim of this descriptive and explorative study was to assess individual case safety reports of bisoprolol associated with tinnitus and investigate their added value in information about adverse drug reactions (ADRs) in relation to information provided in medicine labels. The global reports from VigiBase, the WHO database of individual case safety reports, as of May 3, 2020, were analyzed for information about bisoprolol associated with tinnitus as an ADR affecting the quality of life of the patients. There were 123 reports of the ADR tinnitus reported with intake of bisoprolol in VigiBase. These described experiences of tinnitus and how this impacted on patients' daily life, for example, it could be long‐lasting and may have negative impact on sleeping, and even ability to work and keep a job. There were also reports describing the management of the reaction, for example, recovery upon stopping the treatment, and improvement of the symptoms following a decreased dose or change of medicine batch. Based on reports in VigiBase, the ADR tinnitus associated with bisoprolol suggests vigilance for the onset of the event and that, if it occurs, a dose reduction or stopping the treatment could be necessary. The information provided in the reports shows the value of individual case safety reports collected post marketing, in providing descriptive information of the experience and management of the ADR.